Becoming Pheasant - Eugenie van Heijgen (Humanimalia)
Pheasants have long been considered the most hunted bird species in the world. No other “hunting animal” has been bred, released, and shot for as long and as intensively as the pheasant. In the Netherlands, after centuries of actively shaping these birds and the landscapes in which they were hunted, the rearing and release of pheasants is now prohibited. Yet this hunting legacy still shapes how pheasants are regarded — or disregarded — in contemporary nature conservation and management. By analysing historical hunting documents, interviews, and current policies, I trace how the ecologies, relations, and biological selves that make up pheasants have been shaped by hunting practices. I argue that, because of their ambiguous status derived from this hunting past and the changing nature of contemporary landscapes, pheasants are “unmade” and rendered elusive to conservation efforts. At the same time, pheasants have found ways to re-make themselves and make a living in modern landscapes — paradoxically, still in dialogue with hunters — which might be understood as a form of multi-species stewardship. In this way, pheasants defy labels such as wild, domestic, feral, or native, and shed light on how historically formed interdependencies continue to shape contemporary efforts at biodiversity and nature conservation in Anthropocene landscapes.